The framework for enhancing mathematical higher order thinking skills using technology enhanced learning environment and learning analytics - Rosli, Mohd Shafie; Saleh, Nor Shela; Md. Ali, Azlah; Abu Bakar, Suaibah; Isa, Khairunesa (2024)
Improving the mathematical HOTS of students is a recurring global issue. Substantial evidence indicates that constructivism is a promising learning strategy that is capable of resolving the issue. As digitalisation increases, technologyenhanced learning environments are gaining importance in contemporary education. However, scant literature exists on the process of improving mathematical HOTS while students use technology-enhanced learning environments. The purpose of this paper is to posit a learning process that could improve students' mathematical HOTS based on technology-enhanced learning environments, which were developed through constructivism and tested by the authors using data from learning analytics technology. Sixty samples participated in this study to learn about and interact with technology-enhanced learning environments. Comparing the mathematical HOTS of the samples before and after their interaction with the technologyenhanced learning environments revealed significant differences in the directions of higher HOTS. The sequential analysis technique was applied to 10 759 logs extracted from the learning analytics. Four types of learning engagement activities emerged as a result of empirical testing: Content Engagement, Exercises Engagement, Activities Engagement, and Evaluation Engagement. Analysis utilising Pearson's correlation and linear regression demonstrated that the students' mathematical HOTS were positively affected by their engagement with the content, exercises and activities provided in the technology-enhanced learning environments. The framework was found to be capable of explaining 69% of the mathematical HOTS enhancement process among the samples. This implies that for students' mathematical HOTS to improve or for a technology-enhanced learning environment to have a cognitive implication on students, emphasis must be placed on exercises and online activities. Evaluation was given less weight but remains a necessary component of formal education. This research also demonstrated that, when designed appropriately, technology-enhanced learning environments can enhance students' mathematical HOTS. Therefore, educational technology is a promising solution to the educational problems of the information age